Simulation as a didactic strategy in teacher training practices. Experience in the Social Sciences career (Revista Torreón Universitario, 2020)
This article on educational innovation arises from a process of pedagogical reflection that aimed to use simulation as a teaching strategy to develop pedagogical skills in teachers in training of the social sciences area, in the subject Specialization Practices of the Social Sciences major. The methodology consisted in developing a mixed study, with emphasis on the qualitative approach, applying research techniques such as observation, survey and interviews to the research analysis unit that was composed of twenty-eight students enrolled in the subject. The didactic intervention resulted in the development of the ten teaching skills set out in the subject, which was evident in the simulations that the students carried out during the course of the subject. This study shows that simulation is a didactic strategy that favors the training of education professionals and allows the protagonists to assume roles similar to those they should assume in reality, and therefore, to appropriate the role, knowledge, attitudes, values and skills that this field requires to perform effectively.
Keywords: Social Sciences; teaching skills; didactic strategies; simulation